Legal provision on the use of exotic species in forest restoration: eucalyptus leaf decomposition in different Brazilian savannah formations - Silva, Sarah C. (2023)
The Brazilian federal law has established norms for vegetation protection in 2012 for the planting of exotic species for the restoration of altered areas. Given the large number of areas to be recovered in the savannah biome in Brazil (e.g., Cerrado), the use of fast-growing species and high biomass production (e.g., Eucalyptus spp.) has been earnestly considered. However, the recommendation of this exotic species must be scientifically supported. This work aimed to evaluate the decomposition process of eucalyptus leaf litter in three different phytophysiognomies in the Cerrado biome (Brazilian Savannah) with three different formation type: Typical Cerrado, Savannah Forest, and Gallery Forest. The leaf decomposition was evaluated by the litter bags that were collected from October 2017 to October 2018. The difference between the initial mass and the masses was evaluated at the different collection periods. After one year, we determined the decomposition rate and the constant k using the exponential equation proposed by Olson. The decomposition rate of eucalyptus leaves was high in the three Cerrado formations. The shortest decomposition time was observed in Gallery Forest. The results showed that the main types of Cerrado formation effectively assimilate the organic material to be deposited in the soil. Thus, the study demonstrated the feasibility and legal provision of using exotic species, e.g., eucalyptus in the arduous mission of recovering degraded forest environments.